MENINGKATKAN KEMAMPUAN BERHITUNG SISWA MELALUI MEDIA PAPAN JURANG PADA MATERI OPERASI HITUNG BILANGAN CACAH MATA PELAJARAN MATEMATIKA KELAS III - Selastri Gintulangi; Lian G. Otaya; Asriyati Nadjamuddin (Al-mujahidah, 2026)
This study aims to determine the effectiveness of the use of the panjurang board media in improving the arithmetic ability of third-grade students of SDN 2 Limboto, Gorontalo Regency on the material of arithmetic operations of whole numbers. The type of research used in this study is Classroom Action Research (CAR). Data collection techniques used observation, tests and documentation. The results of this study indicate that there is an increase in students' arithmetic ability after the application of the panjurang media. In the pre-cycle stage, the percentage of students' abilities only reached 58.63%, then increased in cycle I to 82.26%, and continued to increase in cycle II to reach 92.04%. Thus, the difference in the comparison from pre-cycle - cycle I is 23.63%, the difference in the comparison from cycle I - cycle II is 9.78% then from pre-cycle - cycle II has a difference comparison of 33.41%. Students' arithmetic ability is improved through the use of panjurang media which is implemented in two cycles, each consisting of two meetings. Learning activities begin with the preparation stage, including the preparation of learning media to be used and the implementation of observations by researchers during the process.